Supervising Self-Efficacy During the Home Office Using Management Control Systems - Angelova–Stanimirova, Antoaneta (Research Papers, 2023)
Due to the unprecedented circumstances of the last two and a half years, the organizations are facing unprecedented challenges. After the official recommendations for work from home and the re-entry of employees to the office environment – many other questions arise. First, are the employees satisfied that they are back in the office? Is working from home possible? What are the results of the employees’ monitored working time from home? These and many other issues are a major focus of employers in the field of consulting services. The current article aims to explore the concept of self-efficacy and its follow-up based on management control systems. This study is theoretical. Methods of induction and deduction, including analysis and synthesis, are at the article’s core. The results show that well-established management control systems in organizations with consulting services can use the home office as a motivational tool.